Design and Construction of Pharmacy Sales Information System - Sanggita Erinne; agustina srirahayu; Nibras Faiq Muhammad (Universitas PGRI Adi Buana Surabaya, 2025)
Hero Farma Pharmacy in Boyolali serves more than 40 daily transactions but still uses a manual Excel recording system that is prone to human error , data duplication, and slow in reporting. This study aims to create a web-based sales information system to improve the efficiency and accuracy of pharmacy operations. The research method uses a waterfall which includes the stages of needs analysis through interviews and observations, system design with UML, implementation using Laravel 10 and React.js integrated with Inertia.js, and blackbox testing. The implementation results show that the system has been successfully built with a structured database. Blackbox testing on 8 main functions. This web-based information system has succeeded in replacing the manual Excel process , minimizing recording errors, increasing operational efficiency, and supporting better managerial decisions to support pharmacy performance.